Clinical Mastits Incidence In Small-Scale Dairy Cow Farms - Janevski, Aleksandar; Nikolovski, Martin; Cvetkovikj, Iskra; Andreevska, Silvana; Todorovski, Angjelche; Mitrov, Dine (Walter de Gruyter GmbH, 2023)
Abstract The incidence of clinical mastitis (CM) in small and large-scale dairy cow farms can be highly variable and can be affected by age, parity, post-calving status, and atmospheric conditions. The current study aimed to assess the CM-incidence and its association with the post-calving days, number of lactations, season, and number of affected udder quarters in dairy cows in small-scale dairy farms. The study was conducted within one calendar year in 177 small-scale farms with 864 dairy cows. Clinically confirmed CM cows (n=72) were sampled from each udder quarter and processed for bacteriology examination. The CM-positive samples were grouped according to the season (spring, summer, autumn, and winter), the number of days after calving (<90, 90-180, and >180), the number of lactations (1-st, 2-5-th, and >6-th), and the number of affected udder quarters (one, two, three, and four). The CM-positive samples (n=72, 8.3%) were confirmed on bacteriology examination in significantly lower count (n=56, 6.5%). The 2-5-th lactations cows (n=35, 68.6%) were significantly more compared to the first lactation (n=6, 11.8%), and >6-th lactation cows (n=10, 19.6%). CM cows with infection of one udder quarter (n=40, 78.4%) were significantly more than the cows with two (n=6, 11.8%), and four infected quarters (n=5, 9.8%). The CM-incidence in small-scale dairy cow farms in North Macedonia was 8.3% and 6.5% by clinical and bacteriology examination, respectively. The highest CM susceptibility was observed in the cows between the second and fifth lactations. One udder quarter was most frequently affected in CM-positive cases.